Occupational Workload and Work Stress as Correlates of Fasting Blood Glucose among Police Officers in Yogyakarta, Indonesia - Ameelia Rahma Basserawy; Mahendro Prasetyo Kusumo (Published by Institut Teknologi Pendidikan Indonesia, 2026)
Police officers are exposed to high occupational demands that may contribute to psychological stress and metabolic health risks. However, evidence regarding the association between workload, work stress, and fasting blood glucose among Indonesian police officers remains limited. This study examined the association between workload, work stress, and fasting blood glucose among police officers at the Yogyakarta City Police Resort, Indonesia. This cross-sectional study involved 70 active male police officers aged 25–55 years. Workload was measured using the NASA Task Load Index, work stress was assessed using the Perceived Stress Scale-10, and fasting blood glucose was measured using a standardized glucometer. Data were analyzed using Spearman’s rank correlation test with a significance level of p < 0.05. Most respondents had high workload and moderate-to-high work stress. The mean fasting blood glucose level was 150.19 ± 26.74 mg/dL. Workload was positively correlated with fasting blood glucose (r = 0.370; p = 0.002). Work stress was also positively correlated with fasting blood glucose (r = 0.315; p = 0.008). Workload and work stress were significantly associated with fasting blood glucose among police officers. These findings highlight the need for occupational stress management, workload regulation, and routine metabolic screening in police institutions. Further longitudinal studies are needed to clarify causal pathways.